2001
DOI: 10.1007/s11661-001-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of the cruciform specimen geometry to obtain transverse interface-property data in a high-fiber-volume-fraction SiC/Titanium alloy composite

Abstract: A combined experimental and computational methodology was used to determine the relevant strength and residual-stress parameters in a manufactured, high-fiber-volume-fraction multiply metal matrix composite (MMC). The method was similar to that previously demonstrated on single-fiber composites, which had an extremely low fiber volume fraction. Variabilities in residual stresses and debond strengths in high-fiber-volume-fraction multiply composites, as well as current demands on the micromechanics-based comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…To verify the effectiveness of the method cited above, several materials with different mechanical properties, which have been extracted from stress and strain curves produced by various research teams, are studied with the numerical method shown in Table III. [1][2][3][4][5][6][7]38,[41][42][43][44][45][46] The indentation procedures with two indenters, the halfincluded angles of which were 80°and 50°, respectively, are simulated with the finite element method, and the two indentation responses are obtained. The plastic properties of the indented materials are obtained using Eqs.…”
Section: A New Correction For Oandp's Methodsmentioning
confidence: 99%
“…To verify the effectiveness of the method cited above, several materials with different mechanical properties, which have been extracted from stress and strain curves produced by various research teams, are studied with the numerical method shown in Table III. [1][2][3][4][5][6][7]38,[41][42][43][44][45][46] The indentation procedures with two indenters, the halfincluded angles of which were 80°and 50°, respectively, are simulated with the finite element method, and the two indentation responses are obtained. The plastic properties of the indented materials are obtained using Eqs.…”
Section: A New Correction For Oandp's Methodsmentioning
confidence: 99%